CLINICAL SYMPTOMS OF JOINTS DISORDERS IN CHILDREN IN ROSTOV REGION - E.A. Ligostaeva ("Paediatrician" Publishers LLC, 2009)
Heterogeneity of juvenile arthritis conditions the difficulties in estimation of its veritable prevalence among children and in social significance of the disease, leading to early arising of patients' disability. The work analyzes age, demographic and clinical peculiarities of juvenile rheumatoid arthritis in children and adolescents (n = 117), living in Rostov region. It was shown that in Rostov-na-Donu and other cities of Rostov region children had II grade of activity of disease, I and II anatomic grade, II functional class, slowly progressing flow of disease. In rural areas of Rostov region the patients with III grade of activity (67%) were prevalent, and III-IV anatomic class was seen frequently (56%), the degree of disability developing was higher. The clinical course of a disease has slowly progressing character in 79% of patients. The activity of disease, anatomic class and degree of disability in girls are higher than in boys. The articular syndrome is more common in girls and swelling of joints - in boys. The activity of articular syndrome increases in older patients. Key words: children, adolescents, rheumatoid juvenile arthritis, prevalence, clinical peculiarities. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):14-19)